Makna Lirik Lagu Daimei No Nai Kyou (題名のない今日) Karya Hiraidai Kajian Semiotika Sastra - Nur Hastuti; Mayla Faizza (IZUMI, 2023)
Lyrics which are the main composition in a song have a form of communication in the form of words created by the author to express his feelings. This study aims to describe the meaning of the lyrics of the song Daimei no Nai Kyou (題名のない今日) by Hiraida with heuristic reading, hermeneutic reading, and searching for matrices, models, variants, and hypograms. The method used in this study uses the study of literary semiotics as an analytical tool. The data used in this study are the lyrics of the song Daimei no Nai Kyou (題名のない今日) by Hiraida. The theory used is Rifattere's theory of heuristic and hermeneutic reading. Based on the process of reading through heuristics, hermeunistics, models, matrices, and variants, it can be concluded that the description of the meaning of the lyrics of the song Daimei no Nai Kyou is about the meaning of the process of human life. Someone who feels that his life is ordinary and has nothing special to do. However, life is not limited only by the 'alias' or famous nickname that one has. The process of living life is how a person judges himself that all individuals are not the same. Precisely doing small actions that are beneficial to the lives of fellow human beings is a shining kindness. Live your life without having to listen to other people's words and fear what will happen next, just do what you think is good and right. Not only humans feel helped by the kindness given, other living things such as animals and plants also feel the same gratitude.   gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor